Electric and magnetic dipole strength in Sn-112,114,116,118,120,(124) - Bassauer, S.; Von Neumann-Cosel, P.; Reinhard, Paul-Gerhard; Tamii, A.; Adachi, S.; Bertulani, C. A.; Chan, P. Y.; D'Alessio, A.; Fujioka, H.; Fujita, H.; Fujita, Y.; Gey, G.; et al. (Physical Review C - Nuclear Physics, 2020)
Background: There is renewed interest in electric dipole strength distributions for a variety of reasons including the extraction of the dipole polarizability related to properties of the symmetry energy and a measure for the neutron skin thickness, understanding the structure of low-energy E1 strength in nuclei with neutron excess, and establishing the systematics of the isovector giant dipole resonance (IVGDR). Inelastic proton scattering at energies of a few hundred MeV and very forward angles including 0 degrees has been established as a tool for the study of electric and magnetic dipole strength distributions in nuclei.
CRIS-Team WoS Importer:2020-10-23